The Impacts of Interplay and Congruence Between Effectuation and Causation on the Fundraising Opportunities, Successes, and Amount for Startups - Gyehyun Park; KonShik Kim (SAGE Open)
This study explores the impact of the interplay and congruence between effectuation and causation on the fundraising opportunities, successes, and total funding amount for startups. The motivation behind this research lies in the need to understand how different decision-making logics influence startup performance, especially in environments characterized by uncertainty. Effectuation, which focuses on leveraging current means and adapting to changing circumstances, contrasts with causation, which emphasizes goal-driven planning and resource allocation. This study aims to identify the relative value of each approach and determine whether a balanced use of both can enhance startup outcomes. The research utilizes data collected from 304 South Korean startup founders through a two-stage survey, supplemented by financial performance data from 2019 to 2022. Using response surface analysis, this study examines the independent and interactive effects of effectuation and causation on fundraising outcomes. The findings indicate that while the causation approach increases the number of fundraising opportunities, the effectuation approach is more effective in converting these opportunities into successful investments. Furthermore, a congruence effect was found between the two logics, with balanced use resulting in enhanced fundraising opportunities. However, this congruence effect did not translate to the number of successful investments or the total funding amount. These findings contribute to entrepreneurship literature by providing empirical evidence on the complementary roles of effectuation and causation. Practically, the results offer startup founders insights into selecting and balancing decision-making approaches to maximize fundraising opportunities and success in uncertain business environments.